The Conflict of Laws in the Federal State Legal and practical mechanisms to address them-Iraq as a model (Journal of Legal and Political Studies, 2025)
The federal state is a political entity consisting of regional units that have legislative and executive powers within their regional scope, in addition to the federal government that supervises the affairs of the state in accordance. The fact that each region in the federal state has the legislative power may lead to the enactment of laws that may differ from the laws enacted by the federal government, which leads to conflict of laws. This conflict may be temporal, spatial, personal, or hierarchical. The internal conflict of laws, especially spatial conflict in the federal state, is a vital issue that requires finding clear legal solutions to preserve the unity of the state’s legal system and ensure that there is no conflict between federal and local laws. According to the current Iraqi Constitution of 2005, the Kurdistan Region of Iraq has its own legislative powers, which leads to the issuance of local laws that may conflict with federal law. The most important areas that may lead to conflict of laws are investment, personal status laws, and foreign residence laws, which requires finding legal mechanisms to resolve this conflict through the constitution and the precise interpretation of its texts to accurately state the powers granted to the regions, and on cooperation through joint committees between the region and the center to find a mechanism for cooperation to ensure the harmony of laws and reduce disputes and the necessity of coordination between the various authorities to ensure legislative harmony. Emphasis on the role of the supreme courts such as the Federal Supreme Court in adjudicating legal disputes, and it is necessary to adhere to the approach of participation to achieve stability in the federal state. Keywords:federal system, internal conflict of laws, investment, personal status, residence of foreigners
Keywords: Keywordsfederal system; internal conflict of laws; investment; personal status; residence of foreigners